Puig Elias, Segundo Blanco and Sanz (f.l.t.r.) visit the cemetary where Durruti was burried. Series of 3 photos. Copied from CNT collection
Puig Elias, Segundo Blanco and Sanz (f.l.t.r.) visit the cemetary where Durruti was burried. Series of 3 photos. Copied from CNT collection.